Putting outcomes into practice: The implementation of a framework of outcomes measures within a child and family service - Flynn, Susan (My University, 2024)
Of utmost concern for effective child protection and child and family services is evidence-based practice. There is an onus of accountability on providers of therapeutic services to establish the merit and cost efficiency of their work. Developing standardised evidence-based outcome measures for children and families, toward which the service provider can strive, is assuredly required as a yardstick against which progress can be measured and modified. Yet, outcome measures will only work in conducive organisational conditions. Specifically, to operationalise a suite of outcome measures into a complex organisation, from administrative policy to grass roots practice, requires understanding of barriers and facilitators of implementation. Through funded research, we investigate these factors within the implementation of a new outcomes framework in a European child and family service. Following a literature review exercise, qualitative research findings from two focus groups targeted respectively at the managerial and frontline practitioner level, illuminate complex conditions and underlying mechanisms, as well as attitudinal, resource and knowledge factors upon which implementation is predicated. We conclude with recommendations around establishing sustainable conditions and arrangements in organisations, to ensure outcome measures act as effective instruments, rather than costly and dispensable paper exercises.
Keywords: Child and family services; implementation; organisation; outcomes; outcome measures